Insertional mutagenesis of hydrophilic domains in the lactose permease of Escherichia coli. - McKenna, E (1992)
The lactose permease of Escherichia coli is a membrane transport protein postulated to contain a hydrophilic N terminus (hydrophilic domain 1), 12 hydrophobic transmembrane alpha-helices that traverse the membrane in zigzag fashion connected by hydrophilic domains, and a hydrophilic C terminus (hydrophilic domain 13). To test whether the hydrophilic domains are important for function, each domain was independently disrupted by insertion of two or six contiguous histidine residues, and the mutants were characterized with respect to initial rate of lactose transport and steady-state level of accumulation. Remarkably, histidine insertions into 10 out of 13 hydrophilic domains result in molecules that catalyze lactose accumulation effectively, although the initial rate of transport is compromised in certain cases. In contrast, insertions into hydrophilic domain 3, 9, or 10 cause a marked decrease in transport activity. As judged by immunoblots and [35S]methionine pulse-chase experiments, diminished activity is not due to decreased expression of the mutated permeases, defective insertion into the membrane, or increased rates of proteolysis after insertion. The results (i) suggest that most of the hydrophilic domains in the permease do not play an essential role in the transport mechanism and (ii) focus on the region of the permease containing putative helices IX and X as being particularly important for activity.